Assessing equity in the distribution of high-technology medical equipment in Guangxi: evidence from an ethnic minority region in Southern China - Jian Sun; Hai Gu; Qiulin Wen; Hongye Luo (BMC, 2017)
Abstract Background High-technology medical equipment (HTME) are important health resources. However, there is unequal distribution of these equipment in favor of metropolis and well equipped health facilities. This study sought to examine the equity gaps in the distribution of HTME in Guangxi. The results of this study could shed light on the future HTME allocation in Guangxi Zhuang Autonomous Region. Methods Data related to HTME was sourced from a general investigation of all the hospitals of Guangxi. Concentration index was used to assess the equity status of HTME in Guangxi. Results Over all, the total amount of HTME in Guangxi had been increasing from 2011 to 2015, and the per million population HTME of five kinds were all increased at the same time. Meanwhile, the concentration indices ranged between 0.1020 and 0.4617. The five medical equipment were all concentrated among the rich. Conclusions The possession of SPECT per million population in Guangxi is lower than the national average level while it is superior to the national average level for CT, MRI, DSA and LA. The equity status in the distribution of the five medical equipment has deteriorated since 2011. In 2015, the equity status of CT was the best, while the equity status of MRI was the worst. Meanwhile, 45.1% of HTME were concentrated in Nanning, Guilin, and Liuzhou.